Innovation in natural resources: New opportunities and new challenges. The case of the Argentinian seed industry - Marin, Anabel (2015)
In this paper, using the case of seeds, we explore the existence of both new opportunities and new challenges for innovation in Natural Resource Based Industries (NRBIs) in developing countries. Conventional views construe NRBIs as low tech, with low technological dynamism, little innovation, and little capacity to create linkages towards other sectors. However, these views are being increasingly questioned. Some authors argue that although NRs have always provided opportunities for innovation and growth; substantial changes in international institutions, markets and technologies during the last two decades or so have created new and a more diverse set of opportunities for a larger number of developing countries to take advantage of their NRs. We contribute to this literature by providing new empirical evidence that helps to better understand these new opportunities. In addition, we suggest that as new opportunities are being created, new challenges also emerge, and countries which do not comprehend fully both of these might lose the opportunity opened by this historical moment of change to become world leader innovators in NRs and related industries. Empirically we study the case of seeds innovation in Argentina ? a world agricultural leader with a strong and advanced domestic seed industry. Based on firms? interviews and secondary data we show how the new opportunities created for innovation in seeds have been taken by some companies in the developing world and how some new challenges are questioning the capacity to pursue further some of the new opportunities.